Contractualismo y epistemología en las teorías de la tolerancia de Francisco Suárez y John Locke - Fuentes Cobas, Eduardo (Cauriensia, 2024)
In this paper I will argue that the different ways Francisco Suárez and John Locke understand the original contract imply widely different conclusions regarding toleration. Specifically, I will hold that the "strange doctrine" advanced by Locke in his Second Treatise of Government -regarding the right to punish in the state of nature transgressions to the natural law- expresses a "neutralist" epistemological position, which in turns grounds the Letter concerning Toleration’s reasoning. On the contrary, Suárez’s arguments in favor of as well as against toleration, particularly those of De fide, can be explained by a "socially situated" epistemological position, which is consonant with the understanding Suárez has of the birth of the political community.